Recognition of prior learning and identity transformation: Experiences of social work graduates in the Western Cape, South Africa - Williams, Fatima (Department of Social Development, 2024)
This qualitative study aimed to understand the meaning social work graduates who entered university via Recognition of Prior Learning (RPL) attach to their RPL experience and social work education. The goal was to determine whether participation in RPL and studying social work influences identity transformation at a micro level. The researcher intended to address the lacuna in extant knowledge on RPL which focusses on the macro and pedagogical considerations linked to RPL. She is confident that the study provides new knowledge on the influence of RPL and social work education at a micro level. An Interpretative Phenomenological Analysis (IPA) design was used because of the intention to provide an in-depth understanding of the participants' experiences. The study included two universities offering social work programmes in the Western Cape, South Africa i.e. the University of the Western Cape and the University of Cape Town. Five participants were purposively selected from each institution and all the participants completed their social work education in the last five years. Three interviews, using semi-structured interview schedules, were conducted with each participant. The interviews were described and analysed using an amalgamation of the six steps of IPA data analysis. Transformative Learning Theory and Identity Theories were used as theoretical frameworks for the study because these theories address the macro issues related to higher education and account for the internal shifts that university learners can achieve. The results reveal that enrolling in the RPL programme and studying social work had been a transformative learning experience for the participants. The study further reveals that RPL promoted significant identity transformation for the participants and the results allude to the potential of RPL to be transformative at a micro level. The results further revealed that not only did participating in RPL and studying social work influence the participants' identities, but it also influenced their self-awareness and their behaviour. There were challenges with obtaining the sample and evidently RPL is underutilised in social work programmes in South Africa. The thesis thus includes recommendations for future research in RPL and to universities and social work programmes so that RPL can be strengthened.